Challenges in Managing Early Dementia with Multimorbidities in Primary Care - Siaw-Mei, Choong; Yein, Lee Ping; Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2023)
Dementia is one of the most common disabling illnesses associated with aging. About 6.1% of the worldwide population aged 65 years old and above suffers from dementia. Early-onset dementia (EOD) refers to dementia becoming clinically manifested before the age of 65. The prevalence rate of early dementia is 40-100/100,000 in developed countries. Primary causes such as Alzheimer's disease, is the most common cause (50-75%), followed by vascular dementia (20-30%). This case illustrates a 57-year-old lady with underlying diabetes mellitus, hypertension and dyslipidaemia who came for follow-up in the primary care clinic. Her husband complained that she had been having forgetfulness for the past 3 years. This included difficulty in remembering specific routes and she even got lost while driving home. Otherwise, she was still able to manage her basic daily activities including bathing, eating, dressing, grooming and toileting, hence the husband thought that this was common in aging and did not need any intervention or treatment. Her physical examination was unremarkable apart from her MMSE score was 22 out of 30 points, suggestive of mild dementia. The patient was subsequently referred to geriatrics and psychiatry. Her CT scan of the brain showed the presence of a multifocal infarct. The diagnosis of vascular dementia based on the multiple vascular risks and radiological findings was made even though there were physical neurological deficits. This case highlights the challenges in the diagnosis and screening of dementia in primary care. A multidisciplinary approach, an essential role of the family medicine specialist in providing holistic, continuous, coordinated, and comprehensive care to the patient is the cornerstone in managing patients with this diagnosis. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S33